“Comportamiento del musculo del camarón gigante (macrobrachium rosenbergil) durante la deshidratación osmótica utilizando soluciones mixtas de NaCI y sacarosa” - Cajo Pinche, Maria Isabel (2004)
The present work tries on the one dehydrated osmotic, using ternary solutions (NaCl-water-sucrose), give the muscle giant shrimp he/she gives Malaysia, cultivated thoroughly in the department he/she gives San Martin to have a warm-tropical climate, favorable condition for its development; he/she gives easy upbringing ín captivity, it possesses high nutritious valor, with great demand in the domestic market and international, and conserved at the moment by refrigeration and freezing since is highly perecible The composition chemical proximal gives the fresh shrimp determined by the methods he/she gives AOAC (1999), it was proteins 18.42%, lipids 0.98%. humidity 79.08% and ash 1.52%. Previously to the osmotic dehydration it was verified that the shrimp is under good conditions he gives freshness, he was retired the cefalotórax and the exoesqueleto or shell, then the line was submerged in the mean deshidratantes constituted by mixed solutions he/she gives initial concentration he/she gives sacarosa(30, 40 and 50 g. / 100 mi. solution) and give sodium chloride (20, 23 and 26 g. I 100 mi. solution), with a relationship he/she gives volume 4/1, solution I muscle, at 20ºC and with 150 rpm he/she gives agitation. The difusividad gives the salutes in the muscle it was calculated by the well-known mathematical pattem as: second law gives Fick considering to the line like infinite cylinder, through the program Microcal Origin 3.5, being observed good degree gives adjustment. The difusividad gives the sugar it presented securities he/she gives 1.9928 x 10-9 m2/s to 0.8998 x 10-9 m2/s and for the •. salt he/she gives 2.5503 x 10-9 m2/s to 2.1503 x 10-9 m2/s .. The results give osmotic dehydration they show that the penetration gives salt and sucrose is favored in the highest concentrations, while the content gives present humidity in the muscle it presents inverse behavior. The difusiviqªd gives the salutes toward the muscle he/she went smallerAo. more concentration he/she gives the osmotic solution. Give the nine treatments,,·valued organolépticamente the one he/she gives 20 g. give salt with 40 g he/she gives sucrose /100 mi. solution was the one he/she gives bigger acceptance for the panelists, since it presents better sensorial characteristics, realized determination by means of an affective test (method gives scale hedonics he/she gives five puntos). The recount microbiológico threw negative result. The composition chemical proximal gives the dehydrated shrimp it was; proteins 22.09%, lipids 0.41 %. humidity 54.63%, carbohydrates 11.83% and ash 11.04%.